2014
DOI: 10.1155/2014/426898
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prior Hyperthyroidism on Euthyroid Graves’ Ophthalmopathy

Abstract: Background. To investigate the influence of previous exposure to elevated thyroid hormones in euthyroid Graves' ophthalmopathy. Design. Retrospective, observational case series in university setting Median follow-up of 1 year with ranges of 0,8–7,6 years. Study performance of 10 years. Participants. We reviewed the clinical records of 731 Graves' ophthalmopathy patients. There were 88 (12%) patients with onset of Graves' ophthalmopathy during euthyroidism: 37 (5%) patients had ophthalmopathy without known hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…32 and 46) (Table 1). This phenomenon is consistent with a few cases called euthyroid Graves' ophthalmopathy (EGO), which is defined as the presence of thyroid-associated ophthalmopathy in patients with normal thyroid function (40,41). Most of the patients with EGO proved to be TRAb-positive (including stimulating and inhibiting antibodies), but the underlying mechanism is currently unknown (41).…”
Section: Discussionsupporting
confidence: 76%
“…32 and 46) (Table 1). This phenomenon is consistent with a few cases called euthyroid Graves' ophthalmopathy (EGO), which is defined as the presence of thyroid-associated ophthalmopathy in patients with normal thyroid function (40,41). Most of the patients with EGO proved to be TRAb-positive (including stimulating and inhibiting antibodies), but the underlying mechanism is currently unknown (41).…”
Section: Discussionsupporting
confidence: 76%
“…A number of distinct clinical variants of GO exist, however these are poorly studied and deserve attention. Euthyroid/hypothyroid GO is a variant comprising of patients who are euthyroid, or have overt or subclinical hypothyroidism, before or within 6–12 months after the onset of GO and constitutes 0.2–11% of all cases of GO [ 29 33 ]. Patients with GO associated with dermopathy have characteristic skin changes and comprise 1.5% of all cases of GO [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a clinical study conducted by Termote et al , the euthyroid patients developed milder and unilateral ophthalmopathy ( 5 ). The discovery was that previous exposure to high levels of thyroid hormone in euthyroid ophthalmopathy could be associated with proptosis and extraocular muscle restriction ( 5 ). It was also revealed that normal thyroid function influences the course of the GO positively ( 27 ).…”
Section: Clinical Characteristics Of Egdmentioning
confidence: 99%
“…Notably, euthyroid ophthalmopathy can represent the initial stage of thyroid dysfunction. It is also considered that a subset of patients with prior undetermined episodes of transient thyroid abnormalities is identified within the group of euthyroid patients ( 5 ). Long-term follow-up is essential in the management of EGD, and a retrospective study has highlighted that dysthyroidism could occur in 8-25% of patients between 15-45 months from the initial presentation of ophthalmopathy ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation